ANALISIS PENGARUH DIVIDEND PAYOUT RATIO, RETURN ON EQUITY, FIXED ASSET TURNOVER, DAN SALES GROWTH TERHADAP KEBIJAKAN HUTANG (DER) - Yuliana Pratiwi; Prihatiningsih Prihatiningsih; Ida Savitri (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study is based on the problems of consumer goods which is written in the Indonesia Stock Exchange and has a problem with the performance of the company which is shown with the debt level of companies that experienced an upward trend during the period 2013 – 2018. The purpose of this research is to analyze the direction of influence and significance of dividend payout ratio, return on equity, fixed asset turnover, and sales growth toward debt policy at consumer goods industry companies listed in Indonesia Stock Exchange during the period 2013-2018. The population in this research is consumer goods industry companies listed in Indonesia Stock Exchange and sample in this research is 7 (seven) companies at the consumer goods industry companies which is chosen by purposive sampling. Analyze model used in this research is multiple linear regression dated panel analysis model that operated by software eviews 10. The result of the multiple linear regression analysis dated panel model show that (1) The effect of dividend payout ratio toward debt policy is negative and significant (2) The effect of return on equity toward debt policy is positive and significant (3) The effect of fixed asset turnover toward debt policy is negative and significant (4) The effect of sales growth toward debt policy is negative and significant.